Influence of Woven Roving Fiber E-Glass on Electrical Properties of Polyester Composite - Tahir, Dana A; Jamal, Gelas M; Abdullah, Omed Gh (Al-Nahrain Journal of Science, 2018)
The ac conductivity and dielectric permittivity of Polyester filled with different volume fraction of woven roving fiber E-glass prepared by a casting method has been measured, over temperature (23–100)(_^o)C and frequency (40 kHz-1 MHz). It was observed that the ac conductivity increases with increasing frequency and temperature, whereas the dielectric permittivity for all samples shows almost independent on frequency, it was increases with increasing temperature and fiberglass volume fraction. The calculated values of the electrical conductivity shows it was obeys power law Aω^s in which the frequency exponent s is in the range of 0.84